ความเสียหายของอาคารและการประเมินความสูญเสียในเขตกรุงเทพมหานครเนื่องจากแผ่นดินไหว - ปณัยทัต นุตาลัย (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The geological studies found active faults in Kanjanaburi, which could generate a large earthquake that can affect Bangkok, the largest city of Thailand. The objective of this study is to estimate number of damaged buildings at various extents of damage and number of casualties in Bangkok. This information would be useful for planning and preparation for mitigation of earthquake disaster. Assuming that an earthquake had occurred in Kanjanaburi, the distance between earthquake source and the affected area could be determined, and then the ground motion intensity was estimated by a ground motion prediction equation (GMPE), e.g. Chiou and Young (2008). Given the ground motion intensity in term of spectral acceleration or displacement, the probability of buildings being damaged at various levels can be determined from fragility curves. Then, the number of damaged buildings was estimated from the product of total number of buildings and the probability of buildings being damaged. This process of loss assessment can be facilitated by a computer software HAZUS MH-MR 2.1 developed by Federal Emergency Management Agency (FEMA) of USA. In this study, the fragility curves for two most popular buildings in Bangkok, e.g., low- and medium-rise concrete frame buildings were developed by utilizing incremental dynamic analysis (IDA) using ground motions for Bangkok soft soil conditions. All other fragility curves were adopted from USA according to default parameters in the software. The results show that reinforced concrete (RC) buildings, which is the most common building type (68.3% of all buildings), are expectedly the most affected (77.8% of all damaged buildings are RC buildings). The occupancy type of damaged buildings consists of multi-household residential, single-family residential and commercial buildings in proportion of 37.9%, 34.5% and 20.9% of all damaged buildings, respectively. It was also found that estimated number of casualties is 16,949 people if the event occurs during day time (2pm), while fewer casualties (11,011 people) is estimated if the event occurs during night time (2am).